Insights into the mechanism of the symmetry dependent SHG properties in low dimensional KNbO3 structures. Issue 9 (6th April 2023) - Wu, Tianhui; Yin, Baipeng; Bian, Zhenpan; Gao, Yahui; Gu, Jianmin; Wang, Desong
Abstract : The second harmonic generation (SHG) response of low-dimensional nanomaterials is potential dependence on structural symmetry and high-density surface defects, e.g., body contribution and surface contribution. Abstract : The second harmonic generation (SHG) response of low-dimensional nanomaterials is of significant importance for fundamental science and technological applications and shows potential dependence on structural symmetry and high-density surface defects, e.g., body contribution and surface contribution. As surface and body contributions are separable from each other, it is highly desirable to unambiguously evaluate the relative contribution of body and surface on SHG performance. Constructing various polymorphs of a compound with different crystal structures will offer a good opportunity to deduce the quantitative contribution of the body and surface, in which monoclinic, orthorhombic and cubic perovskite-type KNbO3 nanostructures have been prepared through a facile hydrothermal method. Centrosymmetric (CS) cubic KNbO3 nanomaterials show the weakest SHG signal attributed to single surface contribution, while non-centrosymmetric (NCS) orthorhombic and monoclinic KNbO3 nanomaterials exhibit a stronger SHG response because of the synergistic effect of surface and body contributions. Further, the magnitude of surface and body contributions can be effectively deduced, 2.6% and 97.4% in orthorhombic KNbO3 and 1.4% and 98.6% in monoclinic KNbO3, demonstrating that body contribution make overwhelming donations to the SHG response, in which the best SHG performance of monoclinic KNbO3 is rationalized, attributed to the lowest symmetry in the crystal structure.